Conhecimento de pescadores artesanais sobre as populações de toninha (Pontoporia blainvillei) no sudeste e sul do Brasil - Araujo, Samanta Chiste de (2020)
The Franciscana dolphin (Pontoporia blainvillei) is a small endangered cetacean off the South American coastline due to accidental catch by gillnets used in fishing. Information regarding the species and the local ecological knowledge (LEK) of artisanal f